Comparison and correlation between chemical profiles of cephalic salivary glands and cuticle surface of workers of apis mellifera (Hymenoptera, Apidae) - Poiani, Silvana B. [UNESP]; Da Cruz-Landim, Carminda [UNESP] (My University, 2017)
The cuticle surface of insects displays functions in communication, such as recognition. It is known that oenocytes are responsible for the origin of the compounds found in the epicuticle. Secretion of exocrine glands might be added to the original composition during the insect’s life. The aims of the present study were (i) to quantify and to qualify the chemical compounds in cephalic salivary glands (CSG) and cuticle surface of workers of Apis mellifera L., 1758; (ii) to compare chemical profiles of both gland and cuticle; (iii) to verify if the epicuticular and CSG profile compositions allow separation of the workers into phaserelated groups. Glands and wings of newly emerged workers, nurses, and foragers were analyzed by gas chromatography – mass spectrometry. The results have shown that the main compounds in both were hydrocarbons. The Mantel correspondence analysis showed that there was relatively strong correspondence between CSG and cuticular surface in all groups, mainly nurses and foragers. From a total of 37 detected compounds, 29 were the same in both compartments. The results indicated that the gland secretion might be used to replenish the cuticular compounds. In conclusion, glands and cuticle profiles were phaserelated and the CSG may be a potential auxiliary source of cuticular hydrocarbon replenishment in the studied species.
Keywords: Apis mellifera; Cuticular hydrocarbon; Discriminant analysis; GC–MS; Honeybee; Labial gland; Mantel correspondence analysis